Facile Fabrication of Hierarchically Porous Boronic Acid Group-Functionalized Monoliths With Optical Activity for Recognizing Glucose With Different Conformation - Wang, Yan; Zhang, Luwei; Hsu, Yu-I; Asoh, Taka-Aki; Uyama, Hiroshi (Frontiers in Chemistry, 2022)
At present, various materials based on helical polymers are nanoparticle or microsphere, which is not ease of use in practical application. Accordingly, facile preparation hierarchically porous monolith based on helical polymer needs to be developed. Herein, hierarchically porous boronic acid group-functionalized monoliths that exhibited optical activity were fabricated with a facile method based on crosslinking and polymerization-induced phase separation (CPIPS). Chiral substituted acetylene and achiral substituted acetylene with a boronic acid group were used as monomers. By regulating the composition of the pre-polymerization solution, the permeability and macropore size of the porous structure could be controlled. The hierarchically porous structure and large surface area were confirmed by scanning electron microscopy and nitrogen gas adsorption/desorption isotherms. In particular, the boronic acid functional group that can interact with a cis-diol group was successfully introduced on the skeleton surface of the monoliths. Further, the main chain of the copolymer that constituted the monoliths exhibited a high cis content and tacticity, and the monoliths showed good optical activity. Thus, the present study established a facile method to synthesize hierarchically porous boronic acid group-functionalized monoliths with optical activity via CPIPS, and the monoliths showed potential in recognition, separation, and adsorption of compound with chirality and cis-diol groups.